Death strike - Jenkins, Jerry B.; LaHaye, Tim F. (Wheaton, Ill. : Tyndale House, 2000)
As Vicki fights for her life in a detention center, Judd sets a new goal that could put the Young Trib Force in great danger.
Keywords: Christian fiction; Good and evil -- Juvenile fiction; High school students -- Juvenile fiction; Rapture (Christian eschatology) -- Juvenile fiction; Christian fiction; Fantastic fiction